Predicting the origin of soil evidence: High throughput eukaryote sequencing and MIR spectroscopy applied to a crime scene scenario. - Young, Jennifer M; Weyrich, Laura S; Breen, James; Macdonald, Lynne M; Cooper, Alan (Forensic Science International, 2015)
Soil can serve as powerful trace evidence in forensic casework, because it is highly individualistic and can be characterised using a number of techniques. Complex soil matrixes can support a vast number of organisms that can provide a site-specific signal for use in forensic soil discrimination. Previous DNA fingerprinting techniques rely on variations in fragment length to distinguish between soil profiles and focus solely on microbial communities. However, the recent development of high throughput sequencing (HTS) has the potential to provide a more detailed picture of the soil community by accessing non-culturable microorganisms and by identifying specific bacteria, fungi, and plants within soil. To demonstrate the application of HTS to forensic soil analysis, 18S ribosomal RNA profiles of six forensic mock crime scene samples were compared to those collected from seven reference locations across South Australia. Our results demonstrate the utility of non-bacterial DNA to discriminate between different sites, and were able to link a soil to a particular location. In addition, HTS complemented traditional Mid Infrared (MIR) spectroscopy soil profiling, but was able to provide statistically stronger discriminatory power at a finer scale. Through the design of an experimental case scenario, we highlight the considerations and potential limitations of this method in forensic casework. We show that HTS analysis of soil eukaryotes was robust to environmental variation, e.g. rainfall and temperature, transfer effects, storage effects and spatial variation. In addition, this study utilises novel analytical methodologies to interpret results for investigative purposes and provides prediction statistics to support soil DNA analysis for evidential stages of a case.